Human Primary Macrophages Derived In Vitro from Circulating Monocytes Comprise Adherent and Non-Adherent Subsets with Differential Expression of Siglec-1 and CD4 and Permissiveness to HIV-1 Infection - Jobe, Ousman; Kim, Jiae; Tycksen, Eric; Onkar, Sayali; Michael, Nelson L.; Alving, Carl R.; Rao, Mangala (Frontiers in Immunology, 2017)
Macrophages are a major target for human immunodeficiency virus type 1 (HIV-1) infection. However, macrophages are largely heterogeneous and may exhibit differences in permissiveness to HIV-1 infection. This study highlights the interplay of macrophage heterogeneity in HIV-1 pathogenesis. We show that monocyte-derived macrophages (MDM) could be divided into two distinct subsets: CD14+Siglec-1hiCD4+ (non-adherent MDM), and CD14+Siglec-1LoCD4- (adherent MDM). The CD14+Siglec-1hiCD4+MDM subset represented the smaller proportion in the macrophage pool, and varied among different donors. Fractionation and subsequent exposure of the two MDM subsets to HIV-1 revealed opposite outcomes in terms of HIV-1 capture and infection. Although the CD14+Siglec-1hiCD4+MDM captured significantly more HIV-1, infection was significantly higher in the CD14+Siglec-1LoCD4-MDM subset. Thus, CD14+Siglec-1hiCD4+MDM were less permissive to infection. Depletion of CD14+Siglec-1hiCD4+MDM or a decrease in their percentage, resulted in increased infection of MDM, suggestive of a capacity of these cells to capture and sequester HIV-1 in an environment that hinders its infectivity. Increased expression of innate restriction factors and cytokine genes were observed in the non-adherent CD14+Siglec-1hiCD4+MDM, both before and after HIV-1 infection, compared to the adherent CD14+Siglec-1LoCD4-MDM. We speculate that the differential expression of gene expression profiles in the two macrophage subsets may provide an explanation for the differences observed in HIV-1 infectivity.